Influences of Agrochemicals on Health and Ecology in Vietnamese Mango Cultivation - Kiet Hong Vo Tuan Truong; Nguyen Thi Pham; Thoa Thi Kim Nguyen (The Scientific World Journal)
The study aims to identify risks of agrochemicals that impact farmworkers, consumers, and ecology in Vietnamese mango cultivation to enhance safety and friendly production. The study finds out the total numbers of root fertilizers (N-P-K) of the noncooperative and cooperative farmers are similar, approximately 1,400 kg/ha/year higher than those in other countries. Excessive fertilizer usage is a potential threat to soil, water, and air pollution. In addition, the findings indicate that the ecology component is undergoing the most negative impact from excessive agrochemical use in mango farming. The vast majority of agrochemicals in mango cultivation are fungicide and paclobutrazol over 90% of the total number of agrochemicals used in both noncooperative and cooperative farmer groups among the three seasons. Total field EIQ of the cooperative grower category is less than that of the noncooperative grower category. These results show that mango cultivation should consider rejecting the banned active ingredients of glyphosate, paraquat, and carbendazim as well as reducing fungicide and paclobutrazol usage and encouraging cooperative participation to safeguard the environment and human health. Moreover, science information needs to be closely linked and fed back to policy development to boost the management of the awareness of the ecological risks for farmers associated with reducing agrochemical use in mango cultivation.